The Late Palaeozoic Ice Age unconformity in southern Namibia viewed as a patchwork mosaic. (28th September 2021) - Le Heron, Daniel P.; Kettler, Christoph; Griffis, Neil P.; Dietrich, Pierre; Montañez, Isabel P.; Osleger, David A.; Hofmann, Axel; Douillet, Guilhem; Mundil, Roland
Abstract: The expansion of ice masses across southern Africa during the Late Palaeozoic Ice Age has been known for 150 years, including the distribution of upland areas in controlling the configuration of glaciation. In Namibia, increasing attention has focussed on long and deep palaeovalley networks in the Kaokoland region in the north, but comparatively little work has been attempted in the topographically subdued plains of the south, in the Aranos and Karasburg basins. The desert terrain of the Aranos area exposes diamictites of the Dwyka Group discontinuously over about 300 km, extending further south to the Karasburg area at the Namibian‐South African border along the Orange River. Whilst examined at a stratigraphic level, the nature of the contact between the Dwyka glacial rocks and underlying lithologies has not been systematically investigated. This paper presents the results from fieldwork in austral winter 2019, in which a highly varying basal contact is described that records the processes of growth, flow and expansion of ice masses across this part of Gondwana. At the basin margins, subglacially produced unconformities exhibit classic glacially striated pavements on indurated bedrock. In comparison, the basal subglacial unconformity in the more basinward regions is characterised by soft‐sediment striated surfaces and deformation. In the Aranos Basin, soft‐sediment shear zones originated in the subglacial environment. This type of subglacial unconformity developed over well‐differentiated, unconsolidated, siliciclastic materials. Where ice advanced over more poorly sorted material or cannibalised pre‐existing diamictites, 'boulder‐pavements' recognised as single clast‐thick boulder‐dominated intervals formed. Importantly, these boulder‐pavements are enriched in clasts, which were facetted and striated in‐situ by overriding ice. By integrating measurements of striation orientations, fold vergence and palaeocurrent information, former ice flow pathways can potentially be reconstructed over a wide area. Abstract : Namibia has an outstanding record of the Late Palaeozoic Ice Age, including thick diamictites with dramaic facies changes. The relationship between these diamictites and underlying strata has not been fully investigated until present, and reveals such processes as meltwater, sediment deformation and scouring at work in the subglacial environment. A good understanding of these processes and products is vital to accurate palaeo‐ice sheet reconstructions.